2018
DOI: 10.1183/13993003.00589-2018
|View full text |Cite
|
Sign up to set email alerts
|

The impact of patient choice on survival in chronic thromboembolic pulmonary hypertension

Abstract: Pulmonary endarterectomy (PEA) is the gold standard treatment for operable chronic thromboembolic pulmonary hypertension (CTEPH). However, a proportion of patients with operable disease decline surgery. There are currently no published data on this patient group. The aim of this study was to identify outcomes and prognostic factors in a large cohort of consecutive patients with CTEPH.Data were collected for consecutive, treatment-naive CTEPH patients at the Pulmonary Vascular Disease Unit of the Royal Hallamsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
69
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 41 publications
1
69
0
5
Order By: Relevance
“…In einer französischen Untersuchung wurden Patienten mit CTEPH je nach Operabilität des Befundes in verschiedene Gruppen eingeteilt und 12 Jahre nachbeobachtet [120]. Die mit Abstand beste Überlebenszeit hatten die operativ behandelten Patienten, und zwar unabhängig von ihrem Lebensalter.…”
Section: Chronisch Thromboembolische Pulmonale Hypertonie (Cteph)unclassified
“…In einer französischen Untersuchung wurden Patienten mit CTEPH je nach Operabilität des Befundes in verschiedene Gruppen eingeteilt und 12 Jahre nachbeobachtet [120]. Die mit Abstand beste Überlebenszeit hatten die operativ behandelten Patienten, und zwar unabhängig von ihrem Lebensalter.…”
Section: Chronisch Thromboembolische Pulmonale Hypertonie (Cteph)unclassified
“…Another important limitation not discussed in the report by QUADERY et al [8] is that of determining surgical candidacy. Although each case underwent a multidisciplinary evaluation process, the assessment by the prospective operating surgeon was done remotely.…”
mentioning
confidence: 96%
“…In the study by QUADERY et al [8], the prospective registry from Sheffield (UK) reported on 550 consecutive CTEPH patients enrolled from 2001 to 2014. A multidisciplinary team reviewed each case, with suitability for PEA being assessed remotely by an experienced surgeon at the national reference PEA centre, Papworth Hospital (Cambridge, UK).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For the diagnosis of CTEPH, pulmonary endarterectomy is the first choice for treating CTEPH. 5) The lack of treatment will greatly increase the mortality rate 6) in the long run. Some researchers found that inflammation and abnormal pulmonary endothelial cells play a key role in CTEPH, 7,8) but the concrete mechanism associated with the gene and pathway of CTEPH is not yet clear.…”
mentioning
confidence: 99%